Rare Yet Resilient: The Role of Neonatal Genetic Testing & Rare Disease Prognosis on Parental Psychosocial Outcomes, Coping Mechanisms, & Hospital System Recommendations - Abouhala, Siwaar (Tufts Archival Research Center, 2023)
Approximately 3,500 rare genetic diseases manifest within the first 28 days of infant life, and account for between 20-50% of newborn death. Many of these infants are admitted to the neonatal intensive care unit (NICU), where prior research suggests that parents experience high levels of stress, trauma, and uncertainty. These outcomes prompt the need for further investigation of parental psychosocial outcomes post-NICU discharge.; Thesis (B.A.)--Tufts University, 2023.; Submitted to the Community Health Program.; Keywords: genetic screening, metabolic screening, newborn medicine, rare disease, parental outcomes, psychosocial health, mental health, family health.; Committee: Shalini Tendulkar, Nina Ashford.